Peran Digitalisasi dalam Pengembangan UMKM di Kabupaten Banyumas: Sebuah Systematic Literature Review - Sugiarto Sugiarto; Agus Sunarmo; Agus Faturokhman; Yusriyati Nur Farida (Jurnal Riset Akuntansi Soedirman, 2025)
Digitalization has become one of the key strategies in the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, including in Banyumas Regency. Digital transformation is believed to enhance competitiveness, operational efficiency, market access, and business sustainability of MSMEs. This study aims to systematically review the role of digitalization in MSME development, with a specific focus on the regional context of Banyumas Regency. This research employs a Systematic Literature Review (SLR) method following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Scientific articles were collected from national and international databases, including SINTA, Google Scholar, Scopus, and Web of Science, published between 2019 and 2024. The results indicate that digitalization plays a significant role in improving MSME marketing performance, financial management efficiency, financial inclusion, and business resilience. However, the implementation of digitalization still faces several challenges, such as limited digital literacy, inadequate technological infrastructure, and insufficient institutional support. These findings are expected to provide insights for local governments, academics, and MSME practitioners in formulating digital-based MSME development policies and strategies in Banyumas Regency.